Model of Educational Reconstruction in Integrating Ciayumajakuning Ethnoscience into Chemistry Learning - Anugrah, Indah Rizki; Herani Tri Lestiana; Rena Aprillia Indah Sari (Chemistry Education Department of Education and Teaching Faculty, 2025)
This study aims to reconstruct the ethnoscientific contexts of the Ciayumajakuning region (Cirebon, Indramayu, Majalengka, and Kuningan) into chemistry learning materials using the Model of Educational Reconstruction (MER) framework. A descriptive qualitative design was employed, integrating field surveys, literature review, and expert validation. Data were obtained from 17 respondents and scientific literature related to selected local wisdom contexts. The analysis identified five contexts with strong chemical relevance: batik Mega Mendung, wayang kulit, siraman panjang (jamasan), bata dan genteng Jatiwangi, and peuyeum ketan. Each was analyzed for its scientific structure and mapped against the high school chemistry curriculum within the Merdeka Curriculum framework. Results indicate that these local wisdoms represent diverse chemistry concepts, including organic and inorganic reactions, material transformation, and biochemistry, though their distribution across topics remains uneven. The study demonstrates that MER provides a systematic approach to transforming cultural practices into pedagogically sound learning contexts. The reconstructed models are expected to support the development of contextual, culturally responsive chemistry learning materials that strengthen students’ scientific literacy and appreciation of local culture.